On the numerical evaluation for studying Ohmic dissipation and thermal conductivity impacts on the flow of Casson fluid - Khader, M.M.; Babatin, M.M.; Megahed, Ahmed M. (Case studies in thermal engineering, 2023)
Analysis of a steady flow of a viscous Casson fluid subject to Ohmic dissipation and an induced magnetic field is the main goal here. Through a stretched vertical sheet, the flow is managed. The energy equation is explained in a thermodynamical system along with Ohmic heating. By making the assumption that the viscosity and thermal conductivity are temperature-dependent as described here, an accurate assessment of the heat transfer rate may be carried out. Our research also addresses the effect of slip velocity. There are many applications for thermal flow fields subject to limited spaces and heated walls, including electronic cooling systems, furnaces, cooling towers, and thermal individualities in buildings and rooms, to highlight a few. The governing equations of the current model are generated mathematically in the form of partial differential equations by applying the boundary layer approximations along with these assumptions. Through appropriate transformations, a nonlinear system of differential equations is produced. The approximate solution is then obtained by using the Chebyshev spectral collocation method. The proposed problem is reduced to a nonlinear system of algebraic equations with the help of the properties of Chebyshev polynomials of the third-kind. Diagrams are therefore used to illustrate the significant impact of all controlling parameters on the fluid flow. Further, the local Nusselt number and the skin-friction coefficients’ numerical values are also computed and examined. Results show that the Casson fluid motion is strengthened by the electric and mixed convection characteristics, whereas the magnetic, the slip velocity and viscosity parameters impede the flow motion. Also, the distribution of temperature is amplified by a larger Eckert number.